THE EFFECT OF FAMILY PSYCHOEDUCATION THERAPY FOR THE FAMILY ABILITY IN TAKING CARE PATIENTS WITH SCHIZOPHRENIA - Hasmila Sari (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2014)
Introduction. Schizophrenia is the major cause of dissability in the most productive ages. It affects economic and social family condition so that the family ability needs increasing in taking care of patients with schizophrenia at home to decrease family’s burden. The family ability to take care of family member can be trained by family psychoeducation therapy. The purpose of this study was to identify the effect of family psychoeducation therapy for the family ability in taking care patients with schizophrenia. Method. The research design used quasy experiment method with pre post test without control group design by using family psychoeducation therapy intervention. The research was conducted in Aceh government mental hospital with 18 samples. Intervention was implemented through five sessions of family psychoeducation to indentify the difference the family ability in taking care of patients with schizofrenia before and after the intervention. Result. The result of statistics test which used Wilcoxon’s matched pairs test showed there is no differences significant ability between pre and post intervention (p>0,05) although there is increase the number of respondents which have better psychomotor and cognitive ability after the intervention. Discussion. Assessment psychomotor ability would be better if it is supported by the observation process psychomotor training in directly care by providing the knowledge and practice of structured and consistent with family psychoeducation module. Keywords: schizophrenia, psychomotor, cognitive, psychoeducation